EFEKTIFITAS MODUL AJAR APLIKASI DAN RESPON SISWA MATA PELAJARAN PERENCANAAN BIAYA DAN PENJADWALAN KONSTRUKSI BANGUNAN - Puguh Ariskan Najiyullah; Gde Agus Yudha Prawira Adistana (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
The results of the observations showed that there was a problem, namely that the teaching teachers did notuse effective teaching materials in teaching because the teaching materials used by the subject teacherscould not be accessed by students, so students had difficulty understanding the material. Based on theseproblems, this research seeks to provide encouragement to students to understand the material with the helpof an application-based teaching module so that students are able to easily understand the material and canpersonally access teaching materials anytime and anywhere. The aim of this research is to determine theeffectiveness of application-based teaching modules in the subjects of cost planning and buildingconstruction scheduling, as well as students' responses to the use of application-based teaching modules.The research method used is the pre-experimental design (nondesign) method with the one-group pretestposttest design model. Data collection techniques use pre-test and post-test questions and student responsequestionnaires. Based on the research results found, the effectiveness of the application-based teachingmodule obtained a figure through N-Gain testing, namely 0.76 in the "high" category, and the studentresponse results obtained a percentage of 93.54% in the "very good" category.